Resting Serum Concentration of High-Sensitivity C-Reactive Protein (hs-CRP) in Sportsmen and Untrained Male Adults (Nigerian Journal of Physiological Sciences, 2021)
Summary: There is an inverse relationship between regular physical activity and concentration of serum inflammatory markers, with variations in resting CRP in trained and untrained subjects. The effect of acute and prolonged exercises has been studied on inflammatory markers with dearth of information and controversies on the resting serum values of high sensitivity CRP (hs-CRP). Therefore, this study sought to identify and compare variations that occur in serum levels of high sensitivity CRP in groups of sportsmen (6) and physically active untrained subjects. Eighty-one healthy male participants made up of 21 untrained (control), 10 footballers, 10 athletes, 10 karates, 10 volleyballers, 10 basketballers, and 10 baseballers voluntarily participated in the study. Participants rested while in sitting position for about 30 minutes during which blood pressures and heart rates were taken. 5 mls of venous blood was withdrawn from the antecubital vein of the participants (aseptically) between 7:00 and 10:00 am into lithium heparin bottles following an overnight fast. The supernatant was decanted and centrifuged at 3000 rpm, serum was collected and stored at -20ºC prior to biochemical assay which was done with the use of enzyme linked immunosorbent assay (ELISA) kits for hs-CRP. Differences in the means within the sporting groups were analysed using one-way ANOVA while the difference between the trained sportsmen and untrained young adults was analysed using the independent T-test. Statistical significance was set at p < 0.05. The Mean ±SEM age, weight, height, and BMI of the participants were 22.0±0.8 years, 64.1±2.2 kg, 1.74±0.3 m, and 20.6±0.2 kg/m2 respectively. The resting concentration of hs-CRP (μg/ml) was 1.0±0.2 in the untrained, 2.6±0.7 in footballers, 3.6±2.1 in track athletes, 2.4±0.5 in basketballers, 2.2±0.5 in volleyballers, 2.4±1.3 in baseballers, and 1.7±0.5 in karate respectively. There was no significant difference in the resting hs-CRP amongst the sporting groups, and in the sportsmen and untrained group. Resting serum levels of hs-CRP falls within normal range, and varies insignificantly in groups of sports, and in sportsmen and untrained young male adults. This may suggest that the types of sporting activities or participation in sports has no impact on the resting serum hs-CRP.
Keywords: Resting hs-CRP; Sportsmen; Young male adults